An experimental study of non-coaxial soil behaviour using hollow cylinder testing - Cai, Yanyan (2010)
Non-coaxiality of the principal stress direction and principal strain increment direction has been observed in both numerical modelling and experimental studies. The importance of non-coaxiality has been widely recognised in the geomechnical engineering. Without considering the non-coaxiality in the design may lead to an unsafe soil structure. Therefore, it is essential to understand the non-coaxial soil behaviour better and take it into account in the numerical modelling.